Stability Analysis of Weathered Rock Cut Slope Using Geological Mapping and Laboratory Tests - Madun, Aziman (2002)
A study on determining the stability of weathered rock cut slope using geological mapping and laboratory tests. The study is divided into two parts: field work and laboratory testing. The field study focused on the measurement and analysis of the orientation and characteristics of discontinuity. Identification of rock types, weathering grades and observation of cut slope conditions were also included in the field study. Laboratory testing involved determination of natural moisture content, particle size distribution and shear strength. Discontinuity data were analyzed using stereographical method for identification of potential instabilities. A factor of safety (FOS) analysis was conducted on unstable cut slopes using SWEDGE software and manual calculation It is found that the geological mapping and laboratory tests are feasible for assessing slope stability. The FOS analysis has distinguished 10 slope to be considered as fail whilst the other 6 are consider stable same as field observation.